Urban Green Spaces and Climate Changes: Assessing Ecosystem Services for the Municipality of Sassari (Italy) - Andrea De Montis; Antonio Ledda; Vittorio Serra; Alessandro Manunta; Giovanna Calia (Land, 2025)
Urban green spaces (UGS) supply a wide range of ecosystem services (ESs), which are key to mitigation and adaptation to climate changes. In this study, we focus on two ESs, i.e., greenhouse gas sequestration by terrestrial ecosystems and mitigating the heat island effect through vegetation, as defined by the Common International Classification of Ecosystem Services. The purpose is to support municipalities with characteristics similar to those of the municipality investigated in this study with a rough assessment of ESs through freely available data. The ES delivery capacity assessment relies on the adoption of two indicators: (i) increased carbon storage in forests and (ii) the Heat Island Mitigation Index (HIMI). We applied the method to the UGS of the municipality of Sassari (Italy) and found that the potential amount of carbon storage is 42,052.7 t, while the value of HIMI provided by the green spaces in the homogeneous territorial areas is 67.73%. The methodological approach adopted in this study is potentially applicable in Italian as well as Mediterranean small to medium municipalities to integrate the quantitative assessment of ESs in local planning tools. The novelty of this study lies in the applied practical approach, which is implementable by public bodies lacking data and resources, to assessing prima facie the need for operational climate adaptation and mitigation strategies.